Differential susceptibility to prenatal stress exposure in serotonin transporter-deficient female mice—an epigenetic exploration - Weidner, Magdalena T.; Zöller, Johanna E. M.; Hamann, Catharina S.; Schraut, Karla G.; Ali, Muhammad; Lardenoije, Roy; Eijssen, Lars; Foerstner, Konrad U.; Gorbunov, Nikita; Strekalova, Tatyana; Domschke, Katharina; Schmitt-Böhrer, Angelika G.; et al. (Frontiers in Neuroscience, 2025)
IntroductionEarly-life stress exposure has been linked to an increased risk for the onset of mental disorders. As another factor, an individual’s genetic make-up may also tip the scale towards health or disease, with certain genetic variants mediating differential susceptibility towards the effects of early-life stress or other experiences. The current study investigated the molecular foundation of individual variation in the response to prenatal stress (PS) exposure in wildtype mice as well as in mice deficient for the serotonin (5-hydroxytryptamine, 5-HT) transporter (5-HTT).MethodsTo meet this end, wildtype C57BL6/J dams were mated with 5-Htt+/- C57BL6/J males, after which they were exposed to restraint stress during the last part of gestation. In adulthood, female 5-HTT-deficient PS offspring and their wildtype littermates as well as age-matched control groups completed a behavioural test-battery, after which gene expression and histone 3 lysine 4 tri-methylation (H3K4me3) enrichment, as a marker of epigenetic programming, were measured in hippocampal tissue.ResultsDependent on the 5-Htt genotype, PS offspring showed decreased social behaviour in the 3-chamber sociability test. Notably, we observed a considerable degree of behavioural variation in the observed effect of PS in this social test, which allowed segregation into socially affected (SA) and socially unaffected (SU) mice. Genome-wide mRNA expression profiling of hippocampal tissue revealed a core set of 23 genes to be associated with genotype-specific variation in social behaviour following PS exposure. Whereas H3K4me3 levels did not show profound global changes in relation to the variable effects of PS exposure on social behaviour, the kinesin family member 14 (Kif14) gene, which displayed increased expression in socially unaffected wildtype mice, did show lower levels of H3K4me3 in those same mice, but not in any of the other groups.DiscussionAll in all, differential susceptibility linked to PS exposure displayed 5-Htt genotype-dependent behavioural and transcriptomic profiles, supporting the notion of 5-HT-dependent developmental programming.